PEMANFAATAN API (APPLICATION PROGRAMMING INTERFACE) UNTUK PENGEMBANGAN SISTEM PELAYANAN DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL - Yesi Nurhana Dalimonthe; Anna Dina Kalifia; Saucha Diwandari (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
DUKCAPIL services often face obstacles in receiving services manually, which results in a lack of efficiency in community services. The development of an integrated service system based on websites and mobile applications using API technology is a solution in improving efficiency in population and civil registration document services. Development is carried out using API technology as a link between the system and the application. Tests conducted using the System Usability Scale (SUS) by 56 respondents, resulted in a score of 70.08. The score indicates that the system can facilitate online document services as expected. User satisfaction testing can show that the application of service technology through website systems and mobile applications with API technology can provide significant technological support to DUKCAPIL so that it is expected to increase effectiveness and efficiency in community services.